Drop in : the gender rebels who changed the face of skateboarding - Stoll, Deborah (Dey St., an imprint of William Morrow, 2024)
A bad*ss story of the female, queer, bi, and nonbinary skaters who charted a path to the Olympics and changed the face of skateboarding. Who gets to tell the story of skateboarding? Drop In is the first book to recognize and historicize the female, queer, bi, and nonbinary humans who blazed the path that led to today's more equitable skate culture. It wasn't easy getting here. Like the rest of the world, skateboarding has long been patriarchal. In the 70s, it personified the punk rock, lock-up-your-daughters, middle-finger-to-the-man ethos. In the 80s, it was Miami Vice soundtracks and parachute pants, neon graphics and fingerless gloves. In the 90s it was New York City--graffiti, hip-hop, and skating in the street. Rarely did you see a woman's name in a skate video--either on a deck or behind the lens. The four skateboarders at the heart Drop In defied expectations of gender, talent, physical ability, and mental capacity to fight the status quo: Alana as the first openly nonbinary athlete in Olympic history; Vanessa as a trailblazing runaway, dominating contests while drinking to excess; Marbie as an accidental boundary-breaking trans icon; and Victoria as the skate rookie turned social media sensation. Drop In spotlights their paths from rebellious outsiders to recognized pioneers on the historic stage of the 2021 Tokyo Olympics, where skateboarding made its historic debut. Their experiences reveal a side of skateboarding that's never been recorded, amplifying voices that have, for too long, gone unheard.--Goodreads.com.